2012
DOI: 10.1111/j.1524-4725.2012.02538.x
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Conception and Management Challenges of Malignant Fibrous Histiocytoma

Abstract: Our study is consistent with reports of MFH as an aggressive neoplasm and describes the largest population treated with MMS in 3 decades. The changing conception of MFH, along with a propensity for in-transit metastases, may explain higher contemporary recurrence rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
5
1
Order By: Relevance
“…[2][3][4][5] It is a moderately aggressive sarcoma capable of invading soft tissue and skeletal structures. 6 This tumor has historically demonstrated aggressive behavior in the head and neck region with poor survival. 7 Some studies have found that MFH had a significantly decreased overall survival in the head and neck region compared to the rest of the body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] It is a moderately aggressive sarcoma capable of invading soft tissue and skeletal structures. 6 This tumor has historically demonstrated aggressive behavior in the head and neck region with poor survival. 7 Some studies have found that MFH had a significantly decreased overall survival in the head and neck region compared to the rest of the body.…”
Section: Introductionmentioning
confidence: 99%
“…The malignant fibrous histiocytoma (MFH) is a sarcoma first described by O'Brien and Stout in 1964 and is the most common soft tissue sarcoma of the head and neck . It is a moderately aggressive sarcoma capable of invading soft tissue and skeletal structures . This tumor has historically demonstrated aggressive behavior in the head and neck region with poor survival .…”
Section: Introductionmentioning
confidence: 99%
“…Several MFH subtypes have been described in the literature: storiform-pleomorphic, giant cell, inflammatory, and myxoid [4]. The mean survival of patients without surgery is 11.7 months; it is 23.2 months for patients who undergo surgery [5]. MFHs have been reported to occur with increasing frequency in patients treated with radiotherapy for other malignant diseases; however, no prior exposure to ionizing radiation or history of malignancy was documented in our case.…”
Section: Discussionmentioning
confidence: 99%
“…36 A single-center study, however, found a higher recurrence with MMS at 78% (7/9) compared with WLE at 42% (10/24), although, as with any study, MMS and WLE techniques may vary among centers/surgeons. 45 Given variations in terminology, depth of tumor, and margins, comparing outcomes of superficial UPS with WLE vs. MMS has significant limitations. Rather than combining the data, it is most appropriate to provide a range of outcomes.…”
Section: Depth Of Invasionmentioning
confidence: 99%
“…Dermal lesions are often less aggressive, slower growing, and smaller at the time of diagnosis. [40][41][42][43][44][45][46][47][48] Dermal LMS most commonly occurs on the proximal extremities followed by the head and neck and, compared with subcutaneous tumors, has lower rates of recurrence and metastasis (Fig. 4).…”
Section: Superficial Leiomyosarcoma (Lms)mentioning
confidence: 99%